Thyrotoxic goiter and asymptomatic thyroid nodule as an initial presentation of clear cell renal cell carcinoma: a report of two cases - Mohd Ghani @ Mamat, Khairul Asri; Simran, Sidhu; Raja Gopal, Navarasi S.; Azli, Saiful; Badawi, Mohamed Abdelwahab; Hadi, S. H. M.; Fahmy, Omar (Wolters Kluwer - Medknow Publications and Media, 2019)
Thyroid nodule as a metastasis to renal cell carcinoma (RCC) is rarely found. We present two cases – presented with thyroid nodules and diagnosed as metastatic RCC; one patient had thyrotoxic goiter, whereas the second patient presented with asymptomatic thyroid nodule. Subsequently, hemithyroidectomy and total thyroidectomy were performed, respectively. Then, both patients underwent radical nephrectomy for the primary tumor. At present, patients are under regular oncology follow-up, with no evidence of disease recurrence.